The Effect of Motivation on Organizational Citizenship Behavior (OCB) at Telkom Indonesia in Makassar - Ibrahim, Muhammad Akmal; Aslinda, Aslinda (UI Scholars Hub, 2015)
Telecommunication organization needs to more seriously improve its employee's Organizational Citizenship Behavior (OCB) so that the employee more successfully performs his/her dual role, i.e. facilitating growth and serves the public; since OCB relates positively to the overall performance of the organization. This research examines the effect of extrinsic and intrinsic motivation on employee's OCB through the mediating role of organizational commitment. This research applies quantitative approach with research strategy of survey, where questionnaires are directly distributed to respondents. The respondents are 176 employees of 6 work units. The data analysis applies multiple linear regression. The analysis of this research shows that both extrinsic and intrinsic motivation affect OCB; however, intrinsic motivation gives bigger direct effect than extrinsic motivation does. Organizational commitment mediates the effect of motivation on employee's OCB only through extrinsic motivation. The findings of this study implicate the researchers and the manager to review the extrinsic/intrinsic dichotomy in the study and the practice of motivation to improve organizational commitment and employee's OCB.